Controller design using quantitative feedback theory for thermal power plant process. (September 2019) - Murshitha Shajahan, M.S.; Najumnissa Jamal, D.; Aparna, V.
Abstract: This paper proposes a controller design that is robust to parameter variations occurring in a Thermal Power Plant Process. Real time cold startup data is collected from NLC Tamilnadu Power Limited (NTPL), Tuticorin unit, of 500 MW capacity. This data is used for modelling the coal flow rate, air flow rate and feed water flow rate loops which will be controlled to ultimately control the generated electric power. Quantitative Feedback Theory is a technique used for controller design, obtaining the parameters of the PD controller that promotes robustness in the specified performance even with variations in the plant parameters. For a particular frequency, the magnitude and phase of the open loop gain and phase curve are acquired and solving the resultant equations confers us the tuning parameters of the controller. From the simulation results, it can be highlighted that the controller performs fairly well.